Coastal territories of small rivers in the context of the modern landscape architecture development - Kotlyarova Ekaterina; Oleynikova Polina; Basistaya Sofia (E3S Web of Conferences)
The article presents the first stages of research into the elements of spatial structure of a large city on the example of the coastal territories of small rivers as integral components of the water-green framework of a modern city. The authors proposed a schematization of the relationship between the object and the subject of the study, graphic definition of the place of riverbank territories in the urban environment, as well as the detailing of the functional structure of the city in the context of the relationship with the coastal territories of small rivers in large cities. The scientific approach and the corresponding improved methodology of urban planning and design of small river bank territories that we are developing will allow us to make ecologically effective, economical and socially responsible decisions related to the widespread inclusion of small river bank territories in the economic and economic activity of the settlement and to implement the actual techniques of landscape architecture at the stage of design concepts. At the next stage of the study, we plan to pay attention to environmental, economic, social and functional factors, as well as their interrelated combinations of improving the methods of decision-making regarding the improvement of the coastal territories of small rivers. In the future, our improved methodological approach to urban planning and design of urban (small) riverside territories can be used, among other things, for the subsequent selection of the most effective types of improvements according to the given parameters.